Membros: Educação a distância - ., .. (RENOTE, 2010)
Ana Bertoletti De Marchi - Universidade de Passo Fundo Cleuza Alonso - Universidade Federal de Santa Maria Elisa Boff - Universidade de Caxias do Sul Eliseo Reategui - Universidade Federal do Rio Grande do Sul Evandro Alves - Universidade Federal do Rio Grande do Sul Gilse Falkembach - Universidade Luterana do Brasil - ULBRA Janete Sander Costa - Universidade Federal do Rio Grande do Sul Joice Otsuka - Universidade Federal de São Carlos José Valdeni de Lima - Universidade Federal do Rio Grande do Sul Liane Tarouco - Universidade Federal do Rio Grande do Sul Liliana Passerino - Universidade Federal do Rio Grande do Sul Magda Bercht - Universidade Federal do Rio Grande do Sul Marcelo Foohs - Universidade Federal do Rio Grande do Sul Marcus Basso - Universidade Federal do Rio Grande do Sul Maria Cristina Biazus - Universidade Federal do Rio Grande do Sul - UFRGS Marlise Geller - Universidade Luterana do Brasil Patricia Behar - Universidade Federal do Rio Grande do Sul Querte Mehlecke - Faculdades de Taquara-FACCAT/RS Renato Dutra - MicroPower - Educação e Negócios Ricardo Silveira - Universidade Federal de Santa Catarina Roseclea Medina -Universidade Federal de Santa Maria Sidnei Silveira - Centro Universitário Ritter dos Reis - UniRitter Silvia Meirelles Leite - Universidade Federal de Pelotas Simone Conceição - Universidade de Wiscosin - Estados Unidos Coordenação : José Valdeni de Lima - PPGIE Liane Margarida Rockenbach Tarouco - CINTED/UFRGS Eliseo Reategui - FACED/PGIE - UFRGS